PENGARUH SALES GROWTH, RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia) - Hardiyanti Arsela; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the influence of Sales Growth, Return On Assets and Return On Equity on Stock Prices. Where the independent variables in this study are Sales Growth, Return On Assets, Return On Equity and the dependent variable is the Stock Price. The population used is automotive and component companies listed on the Indonesia Stock Exchange (IDX) for the 2015 to 2017 period. This study uses secondary data in the form of financial reports and annual reports on annual reports of automotive companies listed on the IDX for the period 2015-2017. Sampling uses a purposive sampling technique that is a company that has not suffered losses for 3 consecutive years and used is 11 companies. Data analysis using simple linear regression analysis, multiple linear regression, t test, f test, and test the coefficient of determination using SPSS 23. The results of this analysis indicate that the sales growth variable partially (t test) does not affect the stock prices of automotive companies and components listed on the Indonesia Stock Exchange, the variable return on assets partially (t test) affects the stock prices of registered automotive companies and components on the Indonesia Stock Exchange, the return on equity variable partially (t test) affects the stock prices of automotive companies and components listed on the Indonesia Stock Exchange. Simultaneous test results (f test) show the influence of variable sales growth, return on assets, return on equity on stock prices in automotive companies and components listed on the Indonesia Stock Exchange for the period 2015-2017. Keywords: Sales Growth, Return On Assets, Return on Equity And Stock Prices